(untitled) (Research, Society and Development, 2020)
The objective of this study was to correlate the adequacy of exclusive breastfeeding time with clinical and sociodemographic indicators of puerperal women living in an area of social vulnerability in a municipality in the interior of Rio Grande do Sul. The study was characterized as an observational, transversal and quantitative approach. Participants in the study were 81 mothers, selected for convenience, who had children in follow-up at multiprofessional childcare consultations, at a Family Health Unit located in an area of social vulnerability, attended from June to September, 2018. The Fisher’s exact test and the results were considered significant at a maximum significance level of 5% (p≤0.05). It was observed that the majority of the women were young, lived with the partner, only attended elementary school incomplete and had a gross family income of up to a minimum wage. The predominant delivery was cesarean section, the majority of the children performed an adequate number of childcare consultations, were born at term, with adequate birth weight and presented exclusive breastfeeding time lower than the recommended one, with a mean of 115.9 days. There was no significant association between the variable’s marital status, schooling, number of children, gross family income, type of delivery, number adequacy and child-care consultations, and birth weight classification with the adequacy of exclusive breastfeeding time.